Elastic, silk‐cardiac extracellular matrix hydrogels exhibit time‐dependent stiffening that modulates cardiac fibroblast response. Issue 12 (11th August 2016) - Stoppel, Whitney L.; Gao, Albert E.; Greaney, Allison M.; Partlow, Benjamin P.; Bretherton, Ross C.; Kaplan, David L.; Black, Lauren D.
Abstract: Heart failure is the leading cause of death in the United States and rapidly becoming the leading cause of death worldwide. While pharmacological treatments can reduce progression to heart failure following myocardial infarction, there still exists a need for new therapies that promote better healing postinjury for a more functional cardiac repair and methods to understand how the changes to tissue mechanical properties influence cell phenotype and function following injury. To address this need, we have optimized a silk‐based hydrogel platform containing cardiac tissue‐derived extracellular matrix (cECM). These silk‐cECM hydrogels have tunable mechanical properties, as well as rate‐controllable hydrogel stiffening over time. In vitro, silk‐cECM scaffolds led to enhanced cardiac fibroblast (CF) cell growth and viability with culture time. cECM incorporation improved expression of integrin an focal adhesion proteins, suggesting that CFs were able to interact with the cECM in the hydrogel. Subcutaneous injection of silk hydrogels in rats demonstrated that addition of the cECM led to endogenous cell infiltration and promoted endothelial cell ingrowth after 4 weeks in vivo . This naturally derived silk fibroin platform is applicable to the development of more physiologically relevant constructs that replicate healthy and diseased tissue in vitro and has the potential to be used as an injectable therapeutic for cardiac repair. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 3058–3072, 2016.